Tun formation is not a prerequisite for desiccation tolerance in the marine tidal tardigrade Echiniscoides sigismundi. (December 2016) - Hygum, Thomas L.; Clausen, Lykke K. B.; Halberg, Kenneth A.; Jørgensen, Aslak; Møbjerg, Nadja
Abstract : The so‐called 'tun' state is best known from limno‐terrestrial tardigrades and rotifers that rely on this compact body shape for anhydrobiotic survival. Little is known of tun formation in marine species and the evolutionary origin of the state is presently unknown. Here, we investigate desiccation tolerance and tun formation in the marine tidal echiniscoidean tardigrade, Echiniscoides sigismundi (M. Schultze, 1865). Groups of approximately 20 E. sigismundi sampled from Lynæs (Denmark) were dehydrated on filter paper from seawater as well as ultrapurified water and kept for 48 h at 5 °C, after which they were rehydrated in seawater. The activity and behaviour of the tardigrades was examined under a light microscope, whereas scanning electron microscopy was used for high‐resolution three‐dimensional imaging. When dehydrated from seawater, E. sigismundi enters a tun, however, when exposed to ultrapurified water, the tardigrade swells and becomes incapable of movement, and thus incapable of tun formation. Nonetheless, E. sigismundi tolerates being dehydrated from ultrapurified water, revealing an exceptional and unparalleled resilience towards losing structural integrity. Our results confirm previous investigations, which suggest that tun formation relies on a functional musculature. They further suggest that tun formation may have evolved as a response to elevated external pressure rather than desiccation per se.